School Principal’s Leadership Strategies in Building Collaboration Among the School, Parents, and Community at Madrasah Tsanawiyah Muslimin Indonesia Center - Riana, Dewi; Sudarman, Sudarman; Akhmad, Akhmad; Gede Mulawarman, Widyatmike; Azainil, Azainil; Hidayanto, Dwi Nugroho (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
The principal’s leadership strategy in building collaboration is a series of planned and structured steps taken by the principal to encourage, empower, and unite the school, parents, and the community to actively participate in the educational process at school. This study aims to identify and analyze the principal’s leadership strategies in building effective collaboration between the school, parents, and the community at Madrasah Tsanawiyah Muslimin Indonesia Center (MIC) Samarinda City. This research uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that: (1) The principal implements adaptive and participatory leadership strategies, such as establishing open communication, holding regular meetings, and involving parents and the community in decision-making and school program implementation. (2) The obstacles and challenges faced include a lack of awareness and time from parents, minimal two-way communication, and limited community resources. (3) To overcome these obstacles, the principal conducts communication initiatives, designs attractive collaborative programs, and provides training for parents and the community to better understand their important role in education. (4) The principal also optimizes the role of parents and the community by empowering them in various school activities. The conclusion of this study is that effective and contextual leadership strategies have proven capable of building a solid partnership between the school, parents, and the community, thus contributing positively to improving the quality of learning and strengthening students’ character. Strong collaboration among these three parties is essential to support the improvement of education quality and the holistic development of students. However, the involvement of parents and the community in school activities remains low and is not yet optimally structured, thus requiring the active role of the principal as a leader and facilitator